AN OUTLINE OF THE PALAEOGEOGRAPHIC EVOLUTION OF THE AUSTRALASIAN REGION SINCE THE BEGINNING OF THE NEOPROTEROZOIC - Li Z.X.; Powell C.M. (My University, 2001)
In the last 1000 million years, Australia has been part of two supercontinents: Palaeozoic Gondwanaland and Neoproterozoic Rodinia. Neoproterozoic Australia was covered by shallow epicontinental seas, and, in the late Neoprotero-zoic, by low-latitude glaciers. The breakup of Rodinia along the Tasman Line occurred at the end of the Sturtian glaciation Ž . 760 Ma giving rise to the Palaeo-Pacific Ocean. Gondwanaland formed in the Early Cambrian, at the same time as the Tarim block broke away from northwestern Australia. Westward subduction of the Palaeo-Pacific Ocean along the eastern margin of Australia–Antarctica commenced during the Early Cambrian in northern Victoria Land and in the Middle Cambrian in South Australia, and culminated to the Late Cambrian–Early Ordovician Ross–Delamerian Mountains. In the Ordovician, the magmatic arc retreated from Australia's then-eastern continental margin, forming a marginal sea and offshore island arc. A shallow seaway across Australia in the Late Cambrian and Ordovician gradually gave way to desert-like conditions in Central Australia and the adjacent Canning Basin by Silurian time. The Silurian to mid-Devonian was an interval of rapidly changing palaeogeography in eastern Australia with deep volcanogenic troughs formed in a dextral transtensional tectonic setting. Widespread deformation in the Tasman orogenic zone in the Middle Devonian to Early Carboniferous, was accompanied by the development of an Andean-style magmatic arc along the Pacific continental margin of Australia. The most widespread Phanerozoic mountain-building stage in Central Australia occurred in the Late Devonian to mid-Carboniferous, as part of a world-wide Variscan orogenic episode associated with the collision of Gondwanaland with Laurussia to form Pangea. In the late Visean, Australia drifted rapidly southward from previous low latitudes to a near-polar position. Glacial conditions dominated the Late Carboniferous and earliest Permian. Transtensional basins associated with dextral oroclinal shear along the Panthalassan eastern margin of Australia developed in the Late Carboniferous and persisted until the Late Permian, when an Andean-style magmatic arc was re-established. Large foreland basins inboard of the Late Permian to Early Triassic magmatic arc accumulated major coal deposits during Late Permian volcanic phases, but drastic climatic changes at the end of the Permian, possibly caused by global greenhouse conditions, led to red-bed deposition in the Early Triassic.)
Keywords: Paleoproterozoic; Neoproterozoic; Gondwana; Rodinia; Precambrian::Proterozoic::Neoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Неопротерозойская; Докембрий::Протерозой::Палеопротерозойская